AST-to-platelet ratio as a prognostic factor in patients with decompensated liver cirrhosis - Dukić, Marija; Bogdanović, Jovana; Gmizić, Tijana; Branković, Marija (Medicinski podmladak, 2025)
Introduction: Decompensated liver cirrhosis is a symtomatic, terminal stadium of liver cirrhosis, which occurs by the excange of healthy liver parenhime with fibrous tissue due to longterm inflamation. Many studies have been exploring the role of various factors in transition from stabile to decompensated liver cirrhosis. AST and platelet ratios (APRI score) turned up as a promising one to be further explored. Aim: Our study aims to determine if there is correlation between the APRI score and the prognosis of decompensated liver cirrhosis. Material and Methods: A retrospective study was conducted in the Gastroenterology department in KBC „Bežanijska kosa“ in period from june 2022. to july 2023. This study includes 67 patients, about whom the data were collected from their medical history documents. All patients underwent comprenhensive biochemical blood analyses including hepatogram, and complete blood count upon admission. During hospitalization, abdominal ultrasound and esophagogastroduodenoscopy were also performed. For each patient, based on the available analysis results, the APRI score was calculated. All data were processed using the SPSS statistical program and presented graphically. Results: Based on the results of logistic regression, we find that there is not enough evidence to consider the APRI score a significant predictor of mortailty in patients in this data set (p>0,05). Conclusion: The APRI score can be significantly useful in everyday clinical practice for control and treatment of chronic inflammatory liver diseases, as it is an easily asccessible and a simple method. Further research is needed to explore and confirm its importance on a significantly larger dataset. Keywords: decompensated liver cirrhosis, APRI score, AST, platelets, ethylism